2001
DOI: 10.1093/alcalc/36.5.357
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Lobe Changes in Alcoholism: A Review of the Literature

Abstract: Alcohol can induce a wide spectrum of effects on the central nervous system. These effects can be recognized at the neurophysiological, morphological and neuropsychological levels. Several studies of the effect of alcohol on the frontal lobes were identified for review from MedLine, PsychLIT databases and by manual searching. In this review article, the different changes are examined in detail. Computed tomography studies have reported changes of frontal lobe in alcoholism, while magnetic resonance imaging stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
324
2
28

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 479 publications
(380 citation statements)
references
References 121 publications
26
324
2
28
Order By: Relevance
“…Numerous targeted lesion studies in rats and monkeys have shown that working memory performance depends on the mPFC (24), and alcohol dependence produces long-term impairment in PFC function in humans (25,26). The present results showed that rats with a history of escalation of alcohol intake in a binge-drinking model exhibited impairments in mPFC function during withdrawal, showing that mPFC dysfunction may appear early during the transition from alcohol abuse to alcohol dependence; also, these results suggest that repeated binge and withdrawal episodes in young adults may sensitize the mPFC to additional dysfunction and possibly facilitate the transition to alcohol dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous targeted lesion studies in rats and monkeys have shown that working memory performance depends on the mPFC (24), and alcohol dependence produces long-term impairment in PFC function in humans (25,26). The present results showed that rats with a history of escalation of alcohol intake in a binge-drinking model exhibited impairments in mPFC function during withdrawal, showing that mPFC dysfunction may appear early during the transition from alcohol abuse to alcohol dependence; also, these results suggest that repeated binge and withdrawal episodes in young adults may sensitize the mPFC to additional dysfunction and possibly facilitate the transition to alcohol dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Prior structural neuroimaging studies in alcoholism have focused principally on global atrophic changes in cerebral cortex, white-matter, and cerebellum, plus local effects in hippocampus (62), demonstrating volume reduction (21)(22)(23)63). Smaller right amygdalae have been reported in relatives of alcoholics (56).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore individuals with suppressed delta and theta responses are likely to show deficits in cognitive functions that are mediated by these oscillatory processes. There is ample neuropsychological evidence that supports this view, by demonstrating a wide range of cognitive deficits in the domain of executive functions (including attention, working memory, encoding and retrieval processes) in alcoholics and high risk individuals (Fein et al, 1990;Moselhy et al, 2001;Nixon and Tivis, 1997;Ratti et al, 2002).…”
Section: Introductionmentioning
confidence: 99%